Evaluating public and private sector pensions: The importance of sectoral pay differentials - Frank Eich (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2009)
There is currently a strong perception that public sector pensions are generous relative to those offered in the private sector, leading them to be branded “gold plated”. This study argues that pensions should be considered deferred pay; as such any discussion on the relative generosity of pension entitlements in the public and private sectors ought to be conducted against the backdrop of relative public and private sector pay levels. The available evidence shows that median pay is higher in the public sector than in the private sector, but using this to assess relative pay levels is misleading. This is because median pay hides significant variations in relative pay across the genders, occupations and by location. For example, the range of occupations available in the private sector is wider at the lower end of the skills distribution range than in the public sector; for female workers the highest median annual pay in 2008 could be found in education, which is overwhelmingly in the public sector. There is evidence that public sector pay is relatively generous for employees at the lower end of the income distribution but this does not hold for employees at the upper end of the income distribution. In addition, there is substantial evidence that public sector pay is relatively less generous in the south east of England generally and in London in particular. Compared with the private sector, the public sector compensates its employees too little for living in low amenity and/or high cost areas. As a consequence, the quality of public services varies across the UK, with the public sector especially in the south east finding it difficult to recruit and retain skilled staff. Anyone contemplating a reform of public sector pensions ought to take into account the knock-on effects on recruitment and retention of highly-skilled staff in all parts of the UK, and in the south east in particular. As an (unintended) consequence, any reform of public sector pensions might demonstrate the need to review the public sector pay setting structure more generally.
Keywords: 330; Government policy; Labour market; Occupational pensions; Public sector pensions